Use of Alkali in Traditional Dyeing Technologies with Plants - Anete Karlsone; Jorens Kviesis (Heritage, 2025)
Ethnographic sources provide information about several dye plants that produced reddish colors; however, there is no information on how this process is accomplished. Combining information from written sources with the results of dyeing experiments enables a deeper understanding of the dyeing methods employed in the past. This paper gives insight into the effect of using alkali on obtaining reddish tones in dyeing with Potentilla erecta and Rumex sp. In dyeing experiments, wool yarn was dyed with plant extracts, and the chemical compositions were studied both in plant extracts and in extracts obtained from wool after dyeing. As a result, the red/red-brown color is obtained only under the influence of alkali. Analytical studies of procyanidin (PC) extracts from rhizomes and yarns were performed using infrared spectroscopy (FTIR-ATR) and liquid chromatography coupled with mass spectrometric detection (LC-DAD-MS). Procyanidin extracts of P. erecta and R. acetosa contained monomers identified as (+)-catechin and (-)-epicatechin, as well as dimeric procyanidins of type-A (m/z 575 [M−H]−) and type-B (m/z 577 [M−H]−), along with various types of trimers (m/z 865 [M−H]−; m/z 863 [M−H]−), which were also isolated from dyed wool yarns with a similar composition. The conducted research on the use of alkali with tannin-containing plants contributes to deepening our understanding of the perception of color that existed in the ancient rural environment.